Private Market Financing. (World Economic and Financial Surveys; World Economic and Financial Surveys, 1995)
This paper reports the growing number of low-income countries that are making efforts to resolve their debt problems, often aided by the resources of the debt reduction facility for countries of the International Development Association (IDA). Progress for most, however, remains slow. With the backing of IDA resources and assistance from official bilateral sources, debt buy-backs have been concluded by Bolivia, Guyana, Mozambique, Niger, Sao Tome and Principe, Uganda, and Zambia. Preliminary discussions on similar operations are under way with several other countries. Although most of the major baric debt cases have been resolved, attention still needs to be focused on the problems of low-income countries. In many of these countries, the process of debt restructuring has been delayed owing to economic and political difficulties. To maintain market access on reasonable terms, countries need consistently to implement strong macroeconomic and structural policy programs. Maintenance of such programs is likely to be particularly important in the period ahead, given the high degree of uncertainty with regard to interest rate movements in the industrial countries.